Painless Project Management with FogBugz, Second Edition - Gunderloy, Mike (Apress, 2012)
Like any other developer who wants to actually ship software, I use software management tools. One of the most important tools in my own toolbox is FogBugz. Now on its sixth major release, FogBugz is a complete project management system optimized for software teams. It’s Web-based, so you access most of the functionality through your Web browser. I’ve found this an immense help when working with developers and testers scattered about the Internet, but you can also use FogBugz for projects that are maintained entirely at a single location. In this book, you’ll see why I’m so excited about FogBugz, and learn what it can do for your own software management tasks.